The Impact of Current Opioid Agonist Therapy on Hepatitis C Virus Treatment Initiation Among People Who Use Drugs From the Direct-acting Antiviral (DAA) Era: A Population-Based Study. (14th June 2021) - Bartlett, Sofia R; Wong, Stanley; Yu, Amanda; Pearce, Margo; MacIsaac, Julia; Nouch, Susan; Adu, Prince; Wilton, James; Samji, Hasina; Clementi, Emilia; Velasquez, Hector; Jeong, Dahn; et al.
Abstract: Background: Evidence that opioid agonist therapy (OAT) is associated with increased odds of hepatitis C virus (HCV) treatment initiation among people who use drugs (PWUD) is emerging. The objective of this study was to determine the association between current OAT and HCV treatment initiation among PWUD in a population-level linked administrative dataset. Methods: The British Columbia Hepatitis Testers Cohort was used for this study, which includes all people tested for or diagnosed with HCV in British Columbia, linked to medical visits, hospitalizations, laboratory, prescription drug, and mortality data from 1992 until 2019. PWUD with injecting drug use or opioid use disorder and chronic HCV infection were identified for inclusion in this study. HCV treatment initiation was the main outcome, and subdistribution proportional hazards modeling was used to assess the relationship with current OAT. Results: In total, 13 803 PWUD with chronic HCV were included in this study. Among those currently on OAT at the end of the study period, 47% (2704/5770) had started HCV treatment, whereas 22% (1778/8033) of those not currently on OAT had started HCV treatment. Among PWUD with chronic HCV infection, current OAT was associated with higher likelihood of HCV treatment initiation in time to event analysis (adjusted hazard ratio 1.84 [95% confidence interval CI, 1.50, 2.26]). Conclusions: Current OAT was associated with a higher likelihood of HCV treatment initiation. However, many PWUD with HCV currently receiving OAT have yet to receive HCV treatment. Enhanced integration between substance use care and HCV treatment is needed to improve the overall health of PWUD. Abstract : In this retrospective longitudinal cohort study among 13 803 people who use drugs who were confirmed to have chronic hepatitis C virus (HCV) infection in British Columbia, Canada; current opioid agonist therapy was associated with higher likelihood of HCV treatment initiation.